2016
DOI: 10.1111/acer.13096
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefits of Spleen Tyrosine Kinase Inhibitor Administration on Binge Drinking-Induced Alcoholic Liver Injury, Steatosis, and Inflammation in Mice

Abstract: Background Binge drinking is increasingly recognized as an important cause of liver disease with limited therapeutic options for patients. Binge alcohol use, similar to chronic alcohol consumption, induces numerous deregulated signaling events that drive liver damage, steatosis and inflammation. In this report, we evaluated the role of spleen tyrosine kinase (SYK), which modulates numerous signaling events previously identified linked in the development alcohol-induced liver pathology. Methods A three day al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…It also played a modulating role in immune cell-driven liver inflammation, and hepatocyte cell death at different stages of ALD. Inhibition of SYK activation in the mouse model abrogated alcohol-induced neutrophil infiltration, resident immune cell and inflammasome activation, ERK1/2 mediated NFκB activation and IRF3-mediated apoptosis (Bukong et al, 2016a). It has recently been shown that STING and IRF3 modulate hepatocyte cell death during ALD, thereby, linking ER stress signaling with the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It also played a modulating role in immune cell-driven liver inflammation, and hepatocyte cell death at different stages of ALD. Inhibition of SYK activation in the mouse model abrogated alcohol-induced neutrophil infiltration, resident immune cell and inflammasome activation, ERK1/2 mediated NFκB activation and IRF3-mediated apoptosis (Bukong et al, 2016a). It has recently been shown that STING and IRF3 modulate hepatocyte cell death during ALD, thereby, linking ER stress signaling with the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…( ) Confirming and extending these results, our data show that in both models of ethanol‐induced liver injury, and in particular in the prolonged model in which steatosis is greater, treatment with all BA receptor agonists tested reduces ethanol‐induced FASN protein expression, providing an explanation for the beneficial effects of FXR and TGR5 activation on ALD‐induced liver pathology. ( )…”
Section: Discussionmentioning
confidence: 99%
“…(43) Confirming and extending these results, our data show that in both models of ethanol-induced liver injury, and in particular in the prolonged model in which steatosis is greater, treatment with all BA receptor agonists tested reduces ethanol-induced FASN protein expression, providing an explanation for the beneficial effects of FXR and TGR5 activation on ALD-induced liver pathology. (30,31) Pathogen-associated molecular patterns from bacterial fragments drive TLR4-mediated inflammation. (44) Specifically relevant to ALD is the NLRP3inflammasome, a multiprotein complex primed through TLR4 signaling and activated by release of endogenous damage-associated molecular patterns, such as hepatocyte-derived ATP and uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Binge alcohol exposure causes liver inflammation, steatosis, hepatocyte death, and promotes activation of hepatic stellate cells and fibrogenesis [56]. Thus it is crucial to identify therapeutic agents that target multiple aspects of the disease.…”
Section: Zebrafish Models Of Liver Diseasesmentioning
confidence: 99%